La desigualdad social: desarrollo y desafíos del trabajo social desde la reconceptualización en América Latina = Social inequality: development and challenges of Social Work since reconceptualization in Latin America - Alayón, Norberto; Molina, Maria Lorena (Textos & Contextos (Porto Alegre))
This article aims to answer the question: What are the main ruptures that are born out of the Reconceptualization Movement and what are the main debates that have influenced the professional education? To build our answers, we seek to implicate ourselves in the understanding of the “social problematic” or to transcend the “manifestations of social issue”. We pointed out the relationship of social policy with human rights and citizenship to overcome the understanding of simple tools of control, redistribution mechanisms and consumption stimulus, to identify as well the strategic soil of conquests, enlargement and eligibility of social rights. Everything is connected to the ethical, theoretical, political and methodological current debate. The article concludes with some suggestions concerning possible themes, questions or areas of reflection according to our judgment to continue the debate about Social Work in contemporary Latin America